Perspective-taking across cultures: shared biases in Taiwanese and British adults. Issue 11 (20th November 2019) - Wang, J. Jessica; Tseng, Philip; Juan, Chi-Hung; Frisson, Steven; Apperly, Ian A.
Abstract : The influential hypothesis by Markus & Kitayama (Markus, Kitayama 1991. Psychol. Rev. 98, 224) postulates that individuals from interdependent cultures place others above self in interpersonal contexts. This led to the prediction and finding that individuals from interdependent cultures are less egocentric than those from independent cultures (Wu, Barr, Gann, Keysar 2013. Front. Hum. Neurosci. 7, 1–7; Wu, Keysar. 2007 Psychol. Sci. 18, 600–606). However, variation in egocentrism can only provide indirect evidence for the Markus and Kitayama hypothesis. The current study sought direct evidence by giving British (independent) and Taiwanese (interdependent) participants two perspective-taking tasks on which an other-focused 'altercentric' processing bias might be observed. One task assessed the calculation of simple perspectives; the other assessed the use of others' perspectives in communication. Sixty-two Taiwanese and British adults were tested in their native languages at their home institutions of study. Results revealed similar degrees of both altercentric and egocentric interference between the two cultural groups. This is the first evidence that listeners account for a speaker's limited perspective at the cost of their own performance. Furthermore, the shared biases point towards similarities rather than differences in perspective-taking across cultures.